1949
DOI: 10.1111/j.1748-1716.1949.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the Amount of Hemoglobin and Blood Volume in Connection with Physical Training

Abstract: Summary. In the present paper we report on an investigation in which the amount of hemoglobin determined after the method of SJÖSTRAND (1948) in a number of athletically trained men and women has been compared with that in an average group of the respective sexes. The athletically trained men and women showed considerably higher amounts of hemoglobin and blood volumes than the average material. On the whole, the best trained men deviated by 41%, and the women by 44% from the reference material. In three men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

1959
1959
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 3 publications
7
50
0
Order By: Relevance
“…In contrast, Bass, Buskirk, Jampietro and Mager (22) found no increase in Vpl or Vrbc after three weeks of vigorous physical conditioning and Buskirk (23) was unable to demonstrate differences in Vpl or Vwb per unit of total or fat-free body weight in moderately or rigorously trained athletes and nonathletes. The demonstration by Kjellberg, Rudhe and Sjdstrand (21) of large differences between the blood volumes of athletically trained and untrained persons requires re-examination. The carbon monoxide method which they used is particularly unsuitable for this problem, since 15 per cent of the test dose of gas leaves the blood during the measurement and goes mostly to muscle pigments (25,27 2.…”
Section: Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Bass, Buskirk, Jampietro and Mager (22) found no increase in Vpl or Vrbc after three weeks of vigorous physical conditioning and Buskirk (23) was unable to demonstrate differences in Vpl or Vwb per unit of total or fat-free body weight in moderately or rigorously trained athletes and nonathletes. The demonstration by Kjellberg, Rudhe and Sjdstrand (21) of large differences between the blood volumes of athletically trained and untrained persons requires re-examination. The carbon monoxide method which they used is particularly unsuitable for this problem, since 15 per cent of the test dose of gas leaves the blood during the measurement and goes mostly to muscle pigments (25,27 2.…”
Section: Dicussionmentioning
confidence: 99%
“…Gregersen and Nickerson (3) classified subjects according to somatotype and found that variance of blood volume per unit of body surface area was reduced to an important degree when dealing with extreme body types but not in the middle ranges. Divergent results have been reported concerning the influence of age and of physical training on blood volume (2,(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…As previously discussed, ET males and fernales display sirnilar training-induced augmentations in BV, expressed relative to body mass ( 149). In a more recent study, Mier et ai.…”
Section: Gender Differences In Bvmentioning
confidence: 65%
“…The present study indicates that high output occurs with hypervolemia even in the presence of an elevated hematocrit. These observations in the chronic hypervolemia of polycythemia vera may be compared with the studies of Kjellberg, Rudhe and Sjdstrand in which an augmentation of blood volume and work capacity per heart beat were observed in trained athletes (17). The possible relationship between increased output observed with high altitude polycythemia (18) and altered blood volume would seem to merit study.…”
Section: Discussionmentioning
confidence: 90%